PHRASEOLOGY AS A CULTURAL TOOL IN INTERCULTURAL COMMUNICATION (SCIENCE TIME JOURNAL, 2026)
This article explores the role of phraseology in developing intercultural communication in the context of globalization. Phraseological units such as idioms and fixed expressions are culturally bound and often difficult to interpret in cross-cultural interaction. Using a qualitative and comparative approach, the study analyzes phraseological data from dictionaries, literary texts, media discourse, and spoken communication. The findings show that phraseology reflects cultural values and worldviews and plays an important role in preventing misunderstandings in intercultural communication.